Synthesis of Functionalized Coumarins and Quinolinones by NHC-Catalyzed Annulation of Modified Enals with Heterocyclic C–H Acids - Yetra, Santhivardhana Reddy; Roy, Tony; Bhunia, Anup; Porwal, Digvijay; Biju, Akkattu T (Journal of organic chemistry, 2014)
N-Heterocyclic carbene (NHC) catalyzed lactonization and lactamization of 2-bromoenals with heterocyclic C–H acids proceeding via the α,β-unsaturated acyl azolium intermediates is reported. The reaction furnished coumarin- or quinolinone-fused lactone/lactam derivatives. In addition, results of the enantioselective version of this reaction using chiral NHC are presented.